Evolution of hygrophytic plant species in the Anatolia-Caucasus region: insights from phylogenomic analyses of Cardamine perennials - Kantor, Adam; Kučera, Jaromír; Šlenker, Marek; Breidy, Joêlle; Dönmez, Ali A; Marhold, Karol; Slovák, Marek; Svitok, Marek; Zozomová-Lihová, Judita (Annals of botany, 2023)
BACKGROUND AND AIMS: Southwestern Asia is a significant centre of biodiversity and a cradle of diversification for many plant groups, especially xerophytic elements. In contrast, little is known about the evolution and diversification of its hygrophytic flora. To fill this gap, we focus on Cardamine (Brassicaceae) species that grow in wetlands over a wide altitudinal range. We aimed to elucidate their evolution, assess the extent of presumed historical gene flow between species, and draw inferences about intraspecific structure. METHODS: We applied the phylogenomic Hyb-Seq approach, ecological niche analyses and multivariate morphometrics to a total of 85 Cardamine populations from the target region of Anatolia-Caucasus, usually treated as four to six species, and supplemented them with close relatives from Europe. KEY RESULTS: Five diploids are recognized in the focus area, three of which occur in regions adjacent to the Black and/or Caspian Sea (C. penzesii, C. tenera, C. lazica), one species widely distributed from the Caucasus to Lebanon and Iran (C. uliginosa), and one western Anatolian entity (provisionally C. cf. uliginosa). Phylogenomic data suggest recent speciation during the Pleistocene, likely driven by both geographic separation (allopatry) and ecological divergence. With the exception of a single hybrid (allotetraploid) speciation event proven for C. wiedemanniana, an endemic of southern Turkey, no significant traces of past or present interspecific gene flow were observed. Genetic variation within the studied species is spatially structured, suggesting reduced gene flow due to geographic and ecological barriers, but also glacial survival in different refugia. CONCLUSIONS: This study highlights the importance of the refugial regions of the Black and Caspian Seas for both harbouring and generating hygrophytic species diversity in Southwestern Asia. It also supports the significance of evolutionary links between Anatolia and the Balkan Peninsula. Reticulation and polyploidization played a minor evolutionary role here in contrast to the European relatives.
Keywords: Phylogeny; Turecko; Evropa; Europe; hygrophytic flora; Hyb-Seq; Genetic Variation; phylogenomics; endemism; Anatolia; ecological niche; Cardamine; Turkey; Allopolyploidy; genetická variace; Caucasus; fylogeneze